ILMU, ETIKA, DAN AGAMA: REPRESENTASI ICT ISLAM (ISLAMIC INFORMATION AND COMMUNICATION TECHNOLOGIES) - Maxsi Ary (Cakrawala - Jurnal Humaniora, 2010)
Knowledge, ethic, and religion are three combinations that can’t be detached from life structure. Human created to embrace religion, and religion practiced with ethic values, whereas knowledge build from a series of religious practices and ethic values. Islamic Information and Communication Technologies (Islamic ICT) is a discipline that manifested as representation of knowledge,  ethic, and religion that collaborated on practical-empirical aspect, not separated on knowledge development. Therefore, knowledge, ethic, and religion are a harmonization for human being to work goals. Keywords: knowledge, ethic, religion, Information and Communication Technologies (ICT).